VD_FINDINFO Décision / 2014 / 962 vom 10. September 2014 - VD Tribunal cantonal (2014)
AUDITION OU INTERROGATOIRE, PREUVE ILLICITE, DÉFENSE NÉCESSAIRE | 130 let. b CPP (CH), 131 CPP (CH), 158 CPP (CH)